The Registered Nurses’ Perspectives on the Usage of English Language in the Clinical Area - Mustafar, Masmiza; Ahmad, Aini; Md. Zaini, Muhammad Hanafi (2024)
Registered nurses (RNs) are expected to deliver quality patient care for all walks of life. Thus, there are challenges in terms of communication and understanding in delivering patient care services. The aim of this qualitative research was to analyse the perspectives of RNs on English language. The sampling was a purposive sample of RNs. Online interview sessions were conducted with twenty-four RNs including midwives to answer three research objectives that are to understand the RNs’ views on English language usage in the clinical context, to identify the challenges of English language usage faced by RNs, and to identify the affecting factors of English language usage amongst the RNs. Data were transcribed verbatim and analysed using thematic analysis. The study found that RN’s view English languages usage among them is based on their personal preference, English for communication, speaking is important, portraying professionalism and improve work performance. Results shows that lack of confidence, difficulty in grammar, limited vocabulary, difficulty with accents, and emergency situations are the challenges on English usage among RNs. Finally, factors affecting English usage were found to be the personal preference, speaking colleagues, speaking patients, and promotion opportunity. It is recommended that hospital to provide RNs with English courses. Whereas, RNs are encouraged to practice frequent readings and consistent English speaking